The Transmission of Inequality Across Multiple Generations: Testing Recent Theories with Evidence from Germany - Sebastian Till Braun; Jan Stuhler (The Economic Journal, 2018)
This paper shows that across multiple generations, the persistence of occupational and educational attainment in Germany is larger than estimates from two generations suggest. We consider two recent interpretations. First, we assess Gregory Clark's hypotheses that the true rate of intergenerational persistence is higher than the observed rate, as high as 0.75, and time-invariant. Our evidence supports the first but not the other two hypotheses. Second, we test for independent effects of grandparents. We show that the coefficient on grandparent status is positive in a wide class of Markovian models, and present evidence against its causal interpretation.
Keywords: J62; 330